Model Pengembangan Community Based Tourism Wisata Penawar Sari di Desa Ketapang, Banyuwangi - Dita Ayu Lestari; Windi Habsari; Ryan Yeremia Iskandar; Arya Putra Sundjaja (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Tourism is a sector that is very popular with countries in the world to increase their income. Tourism is also seen as a multidimensional industry that has physical, social, cultural, economic and political characteristics, as the largest and fastest growing industry in the world today. Tourism is developed as one of the strategies to improve the quality of life of the community, therefore Community-based Tourism is present to develop local democracy where decision-making related to tourism activities in the area is carried out by the local community and also considers local priorities. The ideal development of community-based tourism should grow on local initiatives or commonly known as bottom up. Where the development of tourism activities is initiated by the local community and the participation of the local community is quite high. In Banyuwangi itself, there is a tourist destination that is starting to rise to move the tourism sector in its area, namely Penawar Sari tourism located in the Ketapang Village area. Although it grew on local initiatives, the community still does not understand how to maximize tourism activities in their area so that it is more profitable for them as the local community and minimizes the impact caused by tourism. Improper management and without proper planning, it is feared that it will actually become a tourism "bomb" that is detrimental to the local community so that a community-based tourism development model is needed in Penawar Sari Tourism so that the community can later become kings in their own area and take part in decision making and be active in tourism activities in their area. The data for this study were collected using observation methods, in-depth interviews with informants, questionnaires and documentation studies. Informants were determined based on purposive sampling, where informants were selected based on certain specifications. The informants for this observation were. Penawar Sari tourism managers and local communities. The results of this study analyze the existing conditions of tourism in Penawar Sari Tourism and analyze the type of community participation in tourism development and formulate a model of community participation in the development of Penawar Sari Tourism.